Application of the CIPPO Evaluation Model in the Islamic Religious Education Study Program - Nur Asiyah; Karnadi Karnadi; Musthofa Musthofa (At-Taqaddum, 2021)
Universities are required to improve quality, one of which is through accreditation. This study aims to evaluate the quality in the face of accreditation and analyze the constraints and supporting factors. This type of research is evaluation research and uses a qualitative approach. The assessment method is done through document studies, interviews, and observations. The data analysis technique used descriptive qualitative analysis. The study results recommend that the Islamic Religious Education Study Program arrange steps for accreditation preparation using the nine criteria instrument. Context evaluation includes changes to accreditation instruments and curriculum changes. Evaluation of inputs, human resources, infrastructure, and financial accessibility meets quality standards, only lacking in the number of study-based lecturers. The criteria for evaluating the process, learning process, research, and community service have met the quality standard. Criteria for evaluating products scientific works like articles, research journals, books, and publications. Evaluation criteria for outcome components that the quality of study programs is assessed from the competitiveness of graduates and the performance of graduates for the community of stakeholders have met quality standards. The quality evaluation constraint found that the ratio of the number of lecturers was not based on the study program. At the same time, the supporting factor was the increasing number of integrated online services.